"Lock the Doors": Toward a Narrative–Semiotic Approach to Organizational Crisis. (July 2014) - Marsen, Sky
Using a narrative–semiotic approach, this article explores the decisions, plans, and actions involved in dealing with organizational risks and crises. It describes a model, or methodological framework, for crisis analysis as well as for organizational learning aimed at crisis management and prevention. The model is based on the interrelational positioning of the relevant agents (project managers, project team members, and stakeholders), the discourses produced by these agents, and their actions. This model is valuable for understanding the situations, goals, motivations, and anxieties that underlie the risk assessment and actions taken during crises. To illustrate the theoretical discussion, the article analyzes the Columbia Space Shuttle accident of 2003.